2019
DOI: 10.5614/j.eng.technol.sci.2019.51.2.9
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of EEG Changes during Prolonged Simulated Driving for the Assessment of Driver Fatigue

Abstract: Fatigue during driving is the main contributing factor to road accidents. It is influenced by time on task (TOT) and time of day (TOD). Recent electroencephalogram (EEG) research on fatigue assessment has shown a promising result in explaining the fatigue phenomenon. However, different findings exist regarding the best EEG parameters related to fatigue. This study examined EEG changes according to the effect of TOT and TOD and determined the best parameters to distinguish fatigue status. To generate driver fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
3
5
0
Order By: Relevance
“…When exhausted, a driver's θ and α power are significantly higher than those when non-fatigued. As Zuraida et al [ 28 ] noted, the increase in the θ wave is more dominant than those of the others. Meanwhile, other studies demonstrated that deteriorating performance and diminished alertness are accompanied by an increase in θ and a decrease in β activity [ 14 , 60 ].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…When exhausted, a driver's θ and α power are significantly higher than those when non-fatigued. As Zuraida et al [ 28 ] noted, the increase in the θ wave is more dominant than those of the others. Meanwhile, other studies demonstrated that deteriorating performance and diminished alertness are accompanied by an increase in θ and a decrease in β activity [ 14 , 60 ].…”
Section: Discussionmentioning
confidence: 92%
“…The mean value of the 15-min PSDs was used to represent each brain wave as an EEG metric. The EEG parameters of power- α , power- β , power- θ and four ratios of brainwaves ( θ / β , θ /[ α + β ], [ θ + α ]/ β , and [ θ + α ]/[ α + β ]) were analyzed [ 26 , 28 ]. The EEG parameters were selected based on the significant difference found for the four ratios of brainwaves between alert and fatigue in driving conditions; these four ratios of brainwaves were considered to be good indicators of driver drowsiness [ 26 , 45 , 46 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study found that driving for about 2.5 hours resulted in moderate level of fatigue, and that a 15-minute rest period did not return fatigue measures to their baseline values. Previous studies have shown that 2 to 3 hours of driving (following a restful night sleep) generally do not yield excessive fatigue and sleepiness (Zuraida et al, 2019;Puspasari et al, 2018;Wang et al, 2018;Di-Stasi et al, 2012;Craig et al, 2011). However, discrepancies do exist due to differences in experimental settings (field vs. simulator) and also due to inter-individual differences (Ingre et al, 2006).…”
Section: Fatigue and Time On Taskmentioning
confidence: 99%
“…sleep durations prior to the experiment). The work of Zuraida et al (2019), for instance, shows the progression of sleepiness that tended to be linear. In contrast, Puspasari et al (2019) found exponential patterns, particularly for drivers who did not receive enough sleep the night before.…”
Section: Fatigue and Time On Taskmentioning
confidence: 99%